Analisis Kinerja Turbin Uap Sebelum dan Setelah Proses Overhaul di PT PERTAMINA GEOTHERMAL ENERGY Area Kamojang - Elli Prastyo; Indah Dhamayanthie (Program Studi Teknik Kimia, Universitas Pamulang, 2022)
One of the important components in geothermal power generation is steam turbines. One of the decreases in steam turbine performance is caused by excessive workload due to continuous operation. Maintenance of steam turbines through important overhauls is carried out to improve the performance of steam turbines. Actual conditions with ideal conditions are important to know and analyze to know the performance of steam turbines. The operational performance of steam turbines at PT Pertamina Energi Geothermal Area Kamojang can be seen from the value of turbine working specifications (Wt), and isentropic efficiency (ηt). Parameters in the form of inlet pressure (P1), outlet pressure (P2), inlet temperature (T1), outlet temperature (T2), and flow rate (m/s) are searched using the ChemicalLogic SteamTab application and linear interpolation methods to determine the value of enthalpy and entropy. The results were obtained that the value of isentropic enthalpy (h2s) before the overhaul amounted to 2,127.41 kJ/kg and after an overhaul of 2,145.91 kJ/kg. Turbine power value (Ẇt) before overhaul was 30,702.88 kW and after overhaul was 36,304.7 kW. Efficiency after overhaul decreased ±1.4% of efficiency before the overhaul.